2016
DOI: 10.1124/dmd.116.071092
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Clopidogrel Conjugation Metabolism: PK Studies in Man and Mice of Clopidogrel Acyl Glucuronide

Abstract: The existence of a glucuronide conjugate of the major circulating clopidogrel metabolites, called clopidogrel acyl glucuronide (CAG), is already known. However, information regarding its pharmacokinetics (PK), metabolism, and clearance are modest. We investigated in vivo the potential CAG trans-esterification to clopidogrel (reaction occurring in vitro in particular conditions) by administering the metabolite to mice. Experiments were then carried out on men, clopidogrel administered alone or followed by activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Despite its widespread use in clinical settings as an antiplatelet drug (Xie et al, 2011;Saeed et al, 2017), clopidogrel continues to draw attention worldwide. Previous studies demonstrated that clopidogrel undergoes extensive metabolism in the liver (Kazui et al, 2010;Xie et al, 2011;Zhu et al, 2013;Savu et al, 2016;Tai et al, 2016). In the human body, ;85% of ingested clopidogrel is rapidly hydrolyzed to clopidogrel carboxylate (CLP-C, an inactive carboxylic acid form), an immediate metabolite, by hepatic carboxylesterase 1 (Zhu et al, 2013); the remaining 15% is metabolized to clopidogrel active metabolite (CAM) by multiple cytochrome P450-mediated two-step oxidative pathways in the liver (Savi et al, 1992(Savi et al, , 2000Kazui et al, 2010;Xie et al, 2011Xie et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its widespread use in clinical settings as an antiplatelet drug (Xie et al, 2011;Saeed et al, 2017), clopidogrel continues to draw attention worldwide. Previous studies demonstrated that clopidogrel undergoes extensive metabolism in the liver (Kazui et al, 2010;Xie et al, 2011;Zhu et al, 2013;Savu et al, 2016;Tai et al, 2016). In the human body, ;85% of ingested clopidogrel is rapidly hydrolyzed to clopidogrel carboxylate (CLP-C, an inactive carboxylic acid form), an immediate metabolite, by hepatic carboxylesterase 1 (Zhu et al, 2013); the remaining 15% is metabolized to clopidogrel active metabolite (CAM) by multiple cytochrome P450-mediated two-step oxidative pathways in the liver (Savi et al, 1992(Savi et al, , 2000Kazui et al, 2010;Xie et al, 2011Xie et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a mean CAG plasma concentration was 336‐fold higher than a mean clopidogrel plasma concentration (470 vs. 1.4 ng/mL) in patients receiving this drug (Silvestro et al, ). More recently, a study indicated that CAG is confirmed as one of the major terminal metabolite of clopidogrel (Savu et al, ). These data indicated that the glucuronidation of CCA is the major phase II metabolic pathway for the elimination of clopidogrel from the body.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, UGT2B7 exhibits a lower apparent K m value and 3-to The most proportion of the ingested clopidogrel (85%) is hydrolyzed to CCA, and subsequently CCA is glucuronidated to CAG by UGTs (Kazui et al, 2010;Xie et al, 2011). In patients, an observed CCA concentration in plasma was 2736 ng/mL, 3000-fold higher than clopidogrel plasma concentration after taking a single oral dose of 75 mg clopidogrel (Savu et al, 2016), and 10400 ng/mL, also 3000-fold higher than plasma clopidogrel concentration after taking an oral dose of 300 mg clopidogrel (Kim et al, 2016). Similarly, a mean CAG plasma concentration was 336-fold higher than a mean clopidogrel plasma concentration (470 vs. 1.4 ng/mL) in patients receiving this drug (Silvestro et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clopidogrel is prodrug and becomes active in the form of its thiol metabolite in the presence of cytochrome P450 enzymes in the liver while major fraction (approximately 85%) of the administered drug converts into a pharmacologically inactive metabolite, Clopidogrel carboxylic acid 2 . The thiol metabolite binds with P2Y12 receptor of platelets irreversibly and inhibits its aggregation 3 .…”
mentioning
confidence: 99%